Produção, acúmulo e decomposição da serrapilhadeira e repartição da precipitação pluviométrica por espécies da caatinga - Silva, Ane Cristine Fortes da (2014)
This study aimed to establish patterns of dynamics of litter and redistribution of rainfall of Caatinga vegetation. Sampling was done monthly for twenty three months in four areas: degraded, successional primary stage, secondary stage and late stage. We installed 72 collectors of 1.0 mx 1.0 m, with nylon fabric background in three areas. Litter deposited was fractionated into leaves, twigs, reproductive structures and miscellaneous, dried and weighed. To assess the stock of accumulated litter we used metal frame with dimensions of 0.5 mx 0.5 m, thrown randomly and collected monthly, taken to the laboratory for oven drying and weighed. To evaluate the decomposition, 40g of litter were placed in nylon bags (litterbags) mesh 1 mm ², dimensions 20.0 x 20.0 cm, being distributed on the soil surface and removed monthly, cleaned, dried and weighed. To evaluate the contribution of rainfall we used interceptometers installed 1.0 m above the ground surface, distributed under the canopy of six species of the caatinga, which evaluated the stemflow through collecting system installed around the stems of these species. The deposition of litter in the primary stage was 2.631,26 kg ha-1; 3.144,89 kg ha-1 in the secondary stage; 3.144,89 kg ha-1 in the late stage. The fraction of leaves was the largest contributor to the formation of litter in three stages. The degraded area showed greater accumulation of litter and decomposition has been sluggish during the dry period. We conclude that occurred greater litterfall in later stages. The late successional stage showed faster decomposition of litter, the evidence that is a better use of litter in nutrient cycling processes and incorporation of organic matter to the soil. The time required to decompose 50 % of the litter in the later stages of succession was lower indicating greater speed of release and reuse of nutrients by the vegetation. The specie jurema preta with less leaf area and consists of leaflets, showed greater internal precipitation in rain events of greater magnitude. The stemflow was not influenced by DAP and basal area. The water lost by trapping represented the largest proportion of total rainfall in all species studied